2016
DOI: 10.1016/j.jpsychires.2016.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Duration of attenuated positive and negative symptoms in individuals at clinical high risk: Associations with risk of conversion to psychosis and functional outcome

Abstract: Research in individuals at clinical high-risk (CHR) for psychosis has focused on subjects with no more than 12 months of present or worsened attenuated positive symptoms. However, the impact of long duration attenuated positive and/or negative prodromal symptoms on outcomes is unclear. Seventy-six CHR subjects with attenuated positive symptoms and at least moderate severity level negative symptoms rated on the Scale of Prodromal Symptoms (SOPS) were prospectively followed for a mean of 3.0 ± 1.6 years. Social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
2
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 53 publications
7
41
2
8
Order By: Relevance
“…In child and adolescent PRS samples, negative symptoms are of special interest as child and adolescent onset psychosis has a more insidious presentation with higher rates of negative symptoms (Ballageer, Malla, Manchanda, Takhar, & Haricharan, 2005) and is related to worse outcome (Fleischhaker et al, 2005). ANS in PRS child and adolescent samples appears months before APS and is associated with long-term social difficulties (Carrión et al, 2016). As this is a naturalistic study, we wanted to see whether a group of patients would meet ANS inclusion criteria only, and observe the prevalence of these criteria in a help-seeking sample of PRS.…”
Section: Authors Describe the Earlier Stage Of The Traditional Mcgorrmentioning
confidence: 99%
“…In child and adolescent PRS samples, negative symptoms are of special interest as child and adolescent onset psychosis has a more insidious presentation with higher rates of negative symptoms (Ballageer, Malla, Manchanda, Takhar, & Haricharan, 2005) and is related to worse outcome (Fleischhaker et al, 2005). ANS in PRS child and adolescent samples appears months before APS and is associated with long-term social difficulties (Carrión et al, 2016). As this is a naturalistic study, we wanted to see whether a group of patients would meet ANS inclusion criteria only, and observe the prevalence of these criteria in a help-seeking sample of PRS.…”
Section: Authors Describe the Earlier Stage Of The Traditional Mcgorrmentioning
confidence: 99%
“…Negative symptoms are already present in ARMS patients and patients with a first-episode psychosis (FEP) and several studies highlighted their importance regarding the outcome of these patient groups. More severe negative symptoms are related to poorer social and role functioning in ARMS (Carrión et al, 2016;Cotter et al, 2014) and FEP patients (Diaz-Caneja et al, 2015), and negative symptoms represent significant predictors for conversion to psychosis Piskulic et al, 2012;Riecher-Rössler et al, 2009;Valmaggia et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Niendam et al (2007) found that changes in visual memory and processing speed are associated with improvements in the GF:S over time. Carrión et al (2016)) and Schlosser et al (2015) found that negative symptoms predicted scores on the GF:S.…”
mentioning
confidence: 97%